2017
DOI: 10.1039/c6ra28760c
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of antioxidant and detoxifying capacities of some date cultivars (Phoenix dactylifera L.) irrigated with sewage water

Abstract: The objective of the study was to compare the effect of irrigation by municipal water (MW) and sewage water (SW) on antioxidant and detoxifying capacities of some commercial Saudi date cultivars, Agwa, Anbr and Safawi (Phoenix dactyliferaL.).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…In a study of the effect of sewage water irrigation of date palm tree in the antioxidant constituency of three Saudi date cultivars, Abdulaal et al [105] reported higher levels of TP; TF; increased antioxidant activity using ABTS, DPPH, and the formation of phosphor-molybdenum complex test; as well as higher activities of peroxidase, polyphenol oxidase, and glutathione-S-transferase in dates irrigated with sewage water as compared to irrigation with municipal water. The increased level of these parameters was accompanied with higher accumulation of heavy metals (Cr, Cu, Fe, Mn, Pb, and Zn) in the sewage water-irrigated dates.…”
Section: Variation Of Antioxidant Priorities Due To Abiotic Stressmentioning
confidence: 99%
“…In a study of the effect of sewage water irrigation of date palm tree in the antioxidant constituency of three Saudi date cultivars, Abdulaal et al [105] reported higher levels of TP; TF; increased antioxidant activity using ABTS, DPPH, and the formation of phosphor-molybdenum complex test; as well as higher activities of peroxidase, polyphenol oxidase, and glutathione-S-transferase in dates irrigated with sewage water as compared to irrigation with municipal water. The increased level of these parameters was accompanied with higher accumulation of heavy metals (Cr, Cu, Fe, Mn, Pb, and Zn) in the sewage water-irrigated dates.…”
Section: Variation Of Antioxidant Priorities Due To Abiotic Stressmentioning
confidence: 99%
“…[2] Monitoring of HMs in date palm is very crucial as it has ability to grow in diverse climatic conditions and grows easily along the roads, residential zones, rural areas, and industrial zones where they are vulnerable to pick pollutants. [3][4][5] Various elemental analytical instrumental techniques are available now-a-days to assess HMs to safeguard consumers. Among the routine analysis, neutron activation analysis, proton induced X-ray emission, electro thermal atomic absorption, proton induced X-ray emission, and inductively coupled plasma are applied because these methods give good indication of macro and micro minerals from dates.…”
Section: Introductionmentioning
confidence: 99%
“…Date palms fields are irrigated sometimes by using sewage water, which can be hypothesized to HM toxicity. [4] HMs accumulate in various parts of the food crop that leads to a variety of clinical problems in animals and human all over the world. [5,6] Humans are usually exposed to these metals through ingestion or breathing as involuntary act and when their concentration increases, above the maximum allowable levels (MALs) set by WHO/FAO, on set of various diseases is triggered as HMs are known mutagenic, teratogenic, and carcinogenic materials.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the availability of clean freshwater is becoming increasingly limited, more and more places use wastewater for irrigation. In addition to containing valuable macro-and micronutrients, which in optimal concentration might be beneficial for plant growth and development [1], domestic wastewater might also contain a considerable amount of non-biodegradable HMs, which in excess, are able to accumulate in the food chain, potentially causing toxicity symptoms [2,3]. Among the many possible contaminants, cadmium (Cd), chromium (Cr), copper (Cu), lead (Pb), mercury (Hg), nickel (Ni), and zinc (Zn) are the most concerning toxic HMs [3], whose properties and effects on plants are discussed in the Supplementary Materials (Table S1).…”
Section: Introductionmentioning
confidence: 99%